Новые для науки представители родов Gallacanthus Eichler и Menacanthus Neumann (Mallophaga, Menoponidae) - Федоренко, И.А. (Вестник зоологии, 1979)
Description and drawings are presented for two new for science species: Gallacanthus eichleri Fedorenko sp. n., a parasite of Alectoris graeca Meis., the third of the known species of this genus, and Menacanthus campestris Fedorenko sp. n., a parasite of Anthus campestris L.